A FEMINIST STYLISTIC ANALYSIS OF FEMALE REPRESENTATION IN MALAY BEAUTY PRODUCT ADVERTISEMENTS ON INSTAGRAM - Aina Nadhirah, Mohd Zaidi; Humaira, Raslie (2021)
Beyond financial profits, an advertising discourse also impacts the socio-cultural construct of members in a particular community. In the context of sexism, the overt manipulation of gender portrayal and language is still a prevalent advertising practice, especially detectable in advertising activities conducted via social media platforms. This qualitative study investigated the use of language in Malay beauty product advertisements. Anchored on the feminist stylistic framework (Mill, 1998), the textual analysis approach was employed to analyze 150 Malay beauty products advertisements sourced from Instagram. Focusing on the use of language in depicting women and the influence of the language in developing the depiction, the stylistic features in particular were examined based on Verdonk (2002)’s stylistic features guide. Findings showed that the stylistic features used contain traits that are stereotypically prescribed to women. Evidences manifesting in seller’s use of language demonstrates the extensive influence of patriarchy, stereotype and woman sexualisation as a promotional strategy for Malay beauty products. This study aspires to provide evidence-based grounds for improvements to be made on the current social media advertising practice; particularly in terms of language appropriateness and ethics.